From Book to Screen: The Role of Digital Media in Forming Pancasila Student Profiles - Khosiah, Nur; Ameh, Amodu Salisu (CV. Bimbingan Belajar Assyfa, 2023)
This research highlights the role of digital media in forming the profile of Pancasila Students by conducting a bibliometric literature review from the Scopus data set from 2014 to 2024. This research is a systematic literature study that aims to explore and analyze how digital media contributes to students' character education, especially in aspects of cooperation, integrity, independence, critical thinking, creativity, and global diversity. Through an assessment of various relevant scientific publications, this research identifies trends, patterns, and developments in the literature discussing this topic. Research subjects include publications from various scientific journals and research affiliates around the world with a focus on primary school education, which was analyzed using VosViewer bibliometric software. This research shows that there is a lack of literature that highlights the direct relationship between digital media and the character formation of Pancasila Students, especially in the educational context in Indonesia. These shortcomings include the limited number of empirical studies observing the implementation of digital media in educational curricula, as well as the lack of in-depth research on the impact of digital media on Pancasila values. Therefore, this research recommends the need for further studies that focus on empirical evaluation and practical implementation of digital media in student character education. The results of this research also reveal a significant increase in students' critical and creative thinking abilities, as well as a deeper understanding of the values ​​of diversity when digital media is used effectively in the educational process. Overall, this research provides important insights for educators and policymakers to maximize the potential of digital media in developing the profile of Pancasila Learners, as well as guiding further research in this area.